Alticola macrotis Radde 1862 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Alticola macrotis Radde, 1862. Reise in den Süden von Ost-Sibierien, 1:196. TYPE LOCALITY: Siberia, S Krasnoyarsk Krai, E Sayan Mtns. DISTRIBUTION: From Altai (Siberia and Xinjiang) and Sayan Mtns east and northeast through N Mongolia and Lake Baikal region to Region of Olekminski in Yakutsk, Russia. SYNONYMS: altaica, fetisovi, vicina, vinogradovi. COMMENTS: Subgenus Alticola. Ognev (1964) placed this species in the subgenus Alticola, but Gromov and Polyakov (1977) and Pavlinov and Rossolimo (1987) listed it under the subgenus Aschizomys. We follow Ognev until the phylogenetic position of lemminus, the type-species of Aschizomys, is defined relative to species of Alticola. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 503, DOI: 10.5281/zenodo.7353098